DA'I INTERPERSONAL COMMUNICATION IN IMPROVING THE MORALS OF THE PEOPLE OF PULAU BALAI VILLAGE, PULAU BANYAK DISTRICT, ACEH SINGKIL REGENCY - Haddad Alwi Syihab Daulay (Advances In Social Humanities Research, 2023)
This study aims to determine the interpersonal communication carried out by dai in moral development in Deisa Puilaui, Puilaui Sub-district Hall, Many Kabuipatein Aceih singkil, besides that this study is also to find out the morals of the community before the dai who preach in the area. This research method uses qualitative research with a descriptive approach. With five informants consisting of the Village Head, Dai who preaches, and the community. Data collection techniques in this study used interview, observation, and documentation techniques. After the data is collected, it is then analyzed using data reduction, data presentation, and conclusions. The results of the research conducted in this study are that the morals of the people in the area before the arrival of the dai were good enough. This is because there is an institution that regulates every movement and problem that occurs in the community, namely the Customary Institution. The institution helps every behavioral development of its community to have good morals and in accordance with Islamic teachings. Customary institutions also teach some Islamic religious teachings such as speaking good words and teaching them to do good deeds. With the existence of this institution, it is able to control every behavior of its community to have Islamic morals. Compared to other regions, the area of Pulau Balai Village, Pulau Besar District, Aceh Singkil Regency has a high level of Islamic community compared to others. To improve morals in the community, dai use interpersonal communication that is useful to improve morals in the community. Interpersonal communication is used to preach to the community by teaching them the teachings of Islam. Dai collaborates with existing institutions to improve the morals of the community. In addition, the preachers also carry out religious activities by inviting the community to follow every activity carried out such as recitation and other religious learning programs. The level of effectiveness of the use of interpersonal communication in improving community morals has a high intensity of 95%. This success can be seen in the better behavior of the community. The community began to diligently carry out congregational prayers, participate in religious studies such as the recitation of social gathering mothers, and reciting. This proves that interpersonal communication carried out can influence people's personalities to have good morals.